Spreading Kinetics of Herschel-Bulkley Fluids Over Solid Substrates - Zhang, Jie; Gu, Hai; Sun, Jianhua; Li, Bin; Jiang, Jie; Wu, Weiwei (Frontiers in Physics, 2020)
The spreading kinetics of Herschel-Bulkley fluids on horizontal solid substrates was studied theoretically. The evolution equations of film thickness were established in both gravitational and capillary regimes and the dynamic contact angles were derived. Finally, the results were compared with known references. The results show that the yield behavior of the fluids is considered to have a significant impact on the spreading kinetics in both cases. Only when stress is larger than yield stress, the significant flow will occur above the substrate. Spreading zone will be divided into two parts by yield surface: sheared zone and yield zone, which is different from the common Newtonian fluids or power-law non-Newtonian fluids extremely. Below the yield surface (z